Dry and Wet Spell forecasting at Umiam (Meghalaya) for Agricultural Planning - Satapathy, K.K.; Jena, S.K.; Daschaudhuri, D. (Journal of Soil and Water Conservation, 2022)
For agricultural management and planning, it is necessary to know the sequence of dry and wet periods along with forward and backward accumulation of rain water. The yield of crops particularly in rainfed condition depends upon the rainfall pattern. This paper presents the study of rainfall, characteristics qf monsoon, occurrence of dry and wet spell at Umiam (Meghalaya). Markov chain model has been applied through computer program to know the probability of having different conditions of dry and wet weeks and also forward and backward accumulation of rain water suitable for crop production. The study helps in deciding the time at which different crops should be grown in the area and their sequence.